Modeling and fabrication of an electromagnetic levitated micromotor for an application as a gyroscope - Ho, Andrew Kwok Yang. (2008)
The future market for micro-gyroscopes is expected to be extremely large in both the automotive and consumer sectors. Consequently, with the inevitable increase in higher resolution applications, more sensitive and cheaper gyroscopes will be required. This project describes the modeling and fabrication of a novel electromagnetic levitated micromotor for an application as a gyroscope, fabricated by surface micromachining techniques. Previous studies indicate that it has the potential to give higher resolution with lower drift, higher reliability, and lower power consumption and at a lower cost as compared to conventional vibratory gyroscopes. This thesis also covers the fabrication results of the 10 MHz micromotor and the initial fabrication of the 50 MHz micromotor. This fabrication involves two major sections: fabrication of the rotors and stator coils. Various processes and techniques involved in the micro fabrication are detailed in this thesis. These processes include thin film deposition, photolithography and wet and dry etching. It is shown that with optimization of these processes, 2 u\m feature size is achievable with wet etching. Also, a solution to lower the resistivity of the aluminium rotor by fabricating a multi-layer thin film will be presented. The cross-section views of the unoptimized and optimized thin films are shown in this thesis. Future works to produce a fully operational gyroscope with sufficient performance and reliability are recommended at the end of this thesis.